Comparison between intravitreal ranibizumab injection and posterior subtenon triamcinolone acetonide injection at time of cataract surgery for prevention of progression of diabetic macular edema - Mahmoud Mohammed Ahmed Ali Khalil; Hosam Othman Mansour; Ahmed Mohamed Raafat Tawfik; Ahmed Gomaa Elmahdy (BMC Ophthalmology, 2022)
Abstract Background The goal of this work is to assess progression of diabetic macular edema (DME) following intravitreal ranibizumab injection compared to subtenon triamcinolone acetonide injection at cataract operation. Methods Retrospective analysis of 73 eyes of 65 participant with DME, with central macular thickness (CMT) ≥ 300 μm. The included eyes were separated into three groups; phacoemulsification with intravitreal Ranibizumab injection group, phacoemulsification with subtenon Triamcinolone acetonide injection group and phacoemulsification only group. Main measures involved best corrected visual acuity (BCVA) one week, one month and three months post-operative. The CMT was compared preoperative and postoperative (one and three months). Results After 1 month of operation, there was a statistical substantial distinction in the median of CMT between ranibizumab & control group (p < 0.001), between subtenon TA & control group (p < 0.001) and in ranibizumab and subtenon TA group (p = 0.023). After 3 months, the variance between ranibizumab & control group was considerable (p < 0.0001) and the variance between subtenon TA & control group was considerable (p = 0.030). Conclusions Combined phacoemulsification with intravitreal injections of ranibizumab or subtenon triamcinolone acetonide may prevent further progression in CMT in individuals with DME following cataract operation.